Thermodynamic analysis of an isopropanol–acetone–hydrogen chemical heat pump. (31st July 2014) - Guo, Jiangfeng; Huai, Xiulan; Xu, Min
SUMMARY An isopropanol–acetone–hydrogen chemical heat pump is investigated in the ASPEN Plus shell, the influences of some important operation parameters on the six different evaluation criteria are presented, and the different evaluation criteria for the heat pump are also analyzed. The decrease of distillation to feed ratio improves the performance of the chemical heat pump, and the increase of endothermic reaction temperature improves the performance of heat pump based on first law of thermodynamics but weakens the performance of heat pump from the viewpoint of second law of thermodynamics. There exists an optimum reflux ratio in terms of enthalpy efficiency, entransy efficiency, and exergy efficiency, but the performance of heat pump deteriorates as the reflux ratio increases in terms of entropy generation number, revised entropy generation number, and ecological COP. The entransy efficiency tends to integrate the behaviors of enthalpy efficiency and exergy efficiency. Compared with entropy generation number, the behavior of revised entropy generation number is more consistent with the practice. Copyright © 2014 John Wiley & Sons, Ltd.